Merkel Cells Release Glutamate Following Mechanical Stimulation: Implication of Glutamate in the Merkel Cell-Neurite Complex - Higashikawa, Asuka; Kimura, Maki; Shimada, Miyuki; Ohyama, Sadao; Ofusa, Wataru; Tazaki, Masakazu; Shibukawa, Yoshiyuki (Frontiers in Cellular Neuroscience, 2019)
Merkel cells (MCs) have been proposed to form a part of the MC-neurite complex with sensory neurons. Although recent evidence has indicated that mechano-sensitive ion channels, such as transient receptor potential channels and Piezo channels, contribute to the mechanosensory transduction in MCs, the detailed mechanism for intercellular communication between MCs and neurons have yet to be clarified. The present study examined the increases in intracellular free Ca2+ concentration ([Ca2+]i) induced by direct mechanical stimulation of MCs. We also measured [Ca2+]i in the trigeminal ganglion neurons (TGs) following direct mechanical stimulation to the MCs in an MC-TGs coculture. The MCs were isolated from hamster buccal mucosa, while TGs were isolated from neonatal Wistar rats. Both cell populations showed depolarization-induced [Ca2+]i. Direct mechanical stimulation to MCs increased [Ca2+]i, showing stimulation strength dependence. In the MC-TGs coculture, the application of direct mechanical stimulation to MCs resulted in increased [Ca2+]i in the TGs. These changes were significantly suppressed by antagonists of glutamate-permeable anion channels (4,4'-diisothiocyanato-2,2'-stilbenedisulfonic acid; DIDS), and non-competitive antagonist of the N-Methyl-D-aspartate (NMDA) receptors (MK801). Apyrase, an ATP-degrading enzyme, and suramin, a non-selective P2 purinergic receptor antagonist, did not exert inhibitory effects on these [Ca2+]i increases in the TGs following MC stimulation. These results indicated that MCs are capable of releasing glutamate, but not ATP, in response to cellular deformation by direct mechanical stimulation. The released glutamate activates the NMDA receptors on TGs. We suggest that MCs act as mechanoelectrical transducers and establish synaptic transmission with neurons, through the MC-neurite complex, to mediate mechanosensory transduction.